PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. GS BATTERY - Irfan Zidni, Muhamad; Martini, Nelly (Journal for Management Student (JFMS), 2022)
This study further examines the effect of work discipline and motivation on the performance of employees at PT. GS battery. The research was conducted using descriptive quantitative and verification methods, namely collecting, presenting, analyzing, and testing hypotheses, as well as making conclusions and suggestions. Samples were collected using the slovin method with a total sample of 100 respondents from the population of 2019 employees. The data analysis techniques used are scale range analysis and path analysis, Microsoft Excel 2016 computer program, and SPSS version 22. From the results of research data analysis, several conclusions were obtained as follows: Work Discipline at PT. GS Battery is in good criteria, motivation is in good criteria, employee performance is in good criteria. From the results of the analysis there is a correlation between work discipline and motivation with a value of 0.474 which means it has a moderate and two-way correlation because it is positive. There is a partial influence of work discipline of 5.7% on the performance of employees of PT. GS Battery and motivation have an effect of 68.8%. Thus, there is a simultaneous influence of work discipline and motivation on employee performance of 51.4%.